FENOMENA PENYAMAAN PEMBAGIAN WARIS ANTARA ANAK PEREMPUAN DAN LAKI LAKI (Penelitian di DESA CIHERAS KECAMATAN CIPATUJAH KABUPATEN TASIKMALAYA) - Siti Hafsah Auliyah; Abduh, Muhammad (Ahwaluna | Jurnal Hukum Keluarga Islam, 2024)
This study focuses on the phenomenon of equal inheritance distribution between male and female children in Ciheras Village, Cipatujah Subdistrict, Tasikmalaya Regency. This practice contradicts Islamic law, which stipulates that the inheritance division should be 2:1. The purpose of this research is to investigate the factors behind this practice, as well as the Islamic legal perspective on it. The research method used is qualitative, employing descriptive-analytical techniques with a normative-empirical approach. Secondary data comes from relevant literature, while primary data is obtained through direct observation and in-depth interviews with religious figures and local communities. The research findings reveal several factors contributing to the equal inheritance distribution: the economic conditions of the predominantly farming community, efforts to avoid family conflicts, long-standing traditions, and the relatively small amount of inheritance. This practice is applied to maintain family harmony, despite Islamic law not recognizing the faraidh principle. This study provides insights into social transformation and community values influenced by the application of Islamic inheritance law in rural areas.